Cardiovascular complications in patients with acute ischemia of the limbs in the early period of ischemic stroke - Pulyaeva, Inna; Prasol, Vitaliy; Miasoiedov, Kyrylo; Ivanova, Yuliya (ScienceRise: Medical Science, 2020)
Aim. To define risks and complications for patients with the sharp ischemia of lower extremities in the sharp period of stroke after reconstructive surgical treatment for the decline of amount of amputations and sharp violations of cerebral circulation of blood postoperative period. Materials and methods. In the period 2015–2019 based on the Department of Acute Diseases of Vessels of the State Institution «ICUS by. VT Zaitsev NAMNU »we operated 31 patients for acute ischemia of the lower extremities during the period of acute ischemic stroke (namely, within 3–4 weeks after the neurological manifestations). The mean age of the patients was 72.9±1.65 years. Among them are 17 women and 14 men. The diagnosis of acute ischemia of the lower extremities was established in 19 patients, the upper – in 12 patients. Results. All patients (31) were operated; the main blood flow was restored. In 28 cases of patients were performed embolectomy, in 3 cases – bypass surgery. Conclusions. Ultrasound examination of the lower extremities should be performed for patients with acute stroke ischemia with paresis to verify acute lower limb ischemia, which allows timely diagnosis of ischemia and reduce the number of amputations in patients with acute lower limb ischemia I-II degree to 0 %, and the risk of stroke to 3.2 %